Effect of hydrodynamics and laser surface melting on erosion-corrosion of X70 steel pipe elbow in oilfield slurry. (October 2022) - Ajmal, T.S.; Arya, Shashi Bhushan; Maurya, P.; Shariff, S.M.
Abstract: Erosion-corrosion (EC) is a significant cause of pipeline failure in the petrochemical industry. The influence of laser surface melting (LSM) on the EC of API X70 steel was investigated with simulated oilfield slurry (1.5 wt% silica sand). The slurry was circulated continuously in a closed-loop apparatus at 3 m/s velocity and EC tests were performed using electrochemical corrosion and weight loss measurements for the untreated and LSM (2.5 kW) samples located at a 90⁰ pipe elbow. Since the erodent particle velocity and the flow rate are low, the EC was dominated by corrosion. LSM samples exhibited higher EC resistance and hardness due to the surface metallurgy alteration and the EC rate varies within the pipe elbow. The primary reasons for the severe EC rates of electrodes placed at the downstream side of the elbow's extrados (outer face) are the secondary flow effect and higher sand concentration. Highlights: Studied influence of laser surface melting (LSM) on erosion-corrosion (EC) behavior of X70 Steel. Extrados downstream side of pipe elbow underwent severe EC due to hydrodynamics. LSM significantly enhanced EC resistance in comparison with its untreated counterpart. Modification in surface metallurgy and improvement in hardness in melted layer entailed improvement in EC resistance.